DEMOGRAPHIC FACTORS ASSOCIATED WITH CONTENT OF DELUSION AND ITS RELATION WITH HOSTILITY / VIOLENCE AMONG PATIENTS OF SCHIZOPHRENIA AT SIR COWASJEE JAHANGIR INSTITUTE OF PSYCHIATRY - Eshwer Kumar1 , Moin Ansari2 , Darya khan laghari3 , Kazi Humayun Rashid 4 , Saleem.ud.din Rashid5 , Shahnawaz M.K. Dal (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
ABSTRACT INTRODUCTION: Schizophrenia is a severe psychiatric disorder that normally begins in late adolescence or early adulthood period of life. It is characterized by gross distortion of thought, perception, and emotion. OBJECTIVES: The study was aimed to determine the correlation between socio-demographic factors and content of delusions among schizophrenic patients. Also to determine the association of content of delusion with the degree of violence in schizophrenia patients. MATERIAL AND METHODS: This cross-sectional study was conducted in Outpatient department (OPD) of Sir Cowasji Jahangir Institute of Psychiatry (SCJIP), Hyderabad, Sindh. All consecutive adult psychiatric patients of both sex having age between 18 to 60 years, who were reported in OPD of SCJIP during the study period and clinically diagnosed Schizophrenia according to DSM-IV criteria, were included in the study. A total of 173 consecutive schizophrenic patients from the OPD of SCJIP, Hyderabad, Pakistan, were investigated for theme or content of delusion through interviewed by using a semi-structured questionnaire during the study period from Nov 2018 to Jun 2019. Data were analyzed using SPSS version 16. Association was seen by using Pearson’s chi-square test. A P-value of less than 0.05 was considered statistically significant. RESULTS: A total of 173 schizophrenic patients were included in the study. The mean age of study participants was 31.3 ± 9.3 years. Male was 113 (65%) with male to female ration of 2:1. Among study participants 102 (59%) were ever married, 69 (40%) had no formal education and 101 (58%) had no monthly income rely on family. Among the content of delusion, the persecutory delusion was most common 81 (47%) followed by bizarre 52 (30%), grandiose 36 (21%) and the idea of reference 18 (10%) significantly. The frequency of violence was noted in 70 (40 %) participants, among them, 2nd - degree violence was most common 42 (24%). No statistically significant correlation was seen between socio-cultural factors and the most common content of delusion (persecutory, grandiose and idea of reference) except Bizarre delusion. A significant relationship was found between Bizarre and some sociocultural factors (age, education, employment, and monthly income) (P < 0.05). The persecutory delusion was significantly correlated with a history of violence (P= 0.001, P < 0.05) whereas no other content of delusion was found correlated with violence. CONCLUSIONS: The persecutory delusion was the most common content of delusion followed by bizarre, Grandiose and idea of references. Only bizarre delusional content was found associated was sociocultural factors. The persecutory delusion was significantly correlated with any degree of violence.